قضية صفات الله عند المعتزلة وأبي الحسن الأشعري وابن تيمية - Muhammad Syifa’urrahman; Amir Reza Kusuma (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
The debate about the attributes of Allah (sifat-sifat Allah) among the mutakallimmin has become an important issue that is discussed because the issue is directly related to monotheism. The debate is caused by the method of thinking used beings different from one group to another. This paper aims to discuss the debate between Abu Hasan al-Asyari, Ibn Taimiyah and the Muktazilah. This paper is a literature review by analyzing the concept of al-sifaat in the core books of Abu Hasan al-As’ari, Ibn Tamiya, and Muktazilah and comparing the views of these figures with a focus on similarities and differences as well as the causal factors that surround them. This paper confirms that Abu Hasan al-Asyari as a representation of the Ash’ariyah group and Ibn Tamiya as a representation of the Salaf emphasizes that Allah has a predetermined al-sifaat both through the Qur’an and Sunnah, without doing interpretation (ta’wil) and tasybih. In contrast to the Muktazilah who rejects the affirmation (itsbat) of the sifaat of Allah, because the determination (itsbat) for them will have implications for taaddud al-qudama (many substances that are qadim).